2013
DOI: 10.2217/fmb.13.61
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spread of Multidrug-Resistant Escherichia Coli Including ST131 in Different Patient Populations in the Euroregion Meuse–Rhine

Abstract: E. coli ST131 was the most prevalent sequence type in our Euroregional study. It is essential to control the spread of these resistant strains (e.g., with infection-control policies, antibiotic stewardship programs and antibiotic resistance surveillance). In this way we could observe shifts in the prevalence of resistance of the E. coli population and act accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Meanwhile, none of them caused any infection during hospitalization. ST131 is the most prevalent (48.0%) in the southern part of the Netherlands (21). Similar results were also reported out of other countries, such as USA and Korea (22,23).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, none of them caused any infection during hospitalization. ST131 is the most prevalent (48.0%) in the southern part of the Netherlands (21). Similar results were also reported out of other countries, such as USA and Korea (22,23).…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, hospitalization 2 years before, the use of antibiotics within 3 months, and the use of glucocorticoids or immunosuppressive drugs were found to be obviously associated with the carriage of ESBL-producing E. coli. Several epidemiological studies have shown that E. coli ST131 may be a major cause of urinary-tract and bloodstream infections within the community as well as in hospitals or long-term care facilities in Europe, Asia, Africa, North America, and Australia (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Van den Donk et al compared the prevalence of resistance in the cross-border region between Belgium, Germany, and the Netherlands among general practitioners, nursing homes, and ICU isolates and found a significant difference in prevalence of co-amoxiclav and ciprofloxacin resistance among all E. coli isolated between the Netherlands and Belgium, i.e., 27% versus 21%, and 23% and 16%, respectively. No significant differences with Germany were reported [41].…”
Section: Discussionmentioning
confidence: 99%